MarioKart. Off to the races! - Foxe, Steve (New York : Random House, 2023)
Nintendo and Mario Kart fans will love to meet Mario, Luigi, and all their friends and foes as they compete and race to win!
3.1
K-3
Keywords: Mario, Mario -- (Fictitious character) -- Juvenile fiction; Automobile racing -- Juvenile fiction; Automobile racing -- Fiction; Readers (Elementary).; Video game characters -- Juvenile fiction